Continuously tunable Er:Yb:Ca3NbGa3Si2O14 1.5–1.6 μm laser with a broad wavelength range of 102 nm. (February 2023) - Chen, Yujin; Huang, Jianhua; Lin, Yanfu; Gong, Xinghong; Luo, Zundu; Huang, Yidong
Highlights: An Er:Yb:CNGS crystal with broad wavelength tunability in 1.5–1.6 μm was exploited. A continuously tunable 1.5–1.6 μm laser with a wavelength range of 102 nm was realized. The achieved maximum continuous-wave output power of the tunable laser was higher than 100 mW. Abstract: The exploiting of novel Er 3+ /Yb 3+ co-doped material with broad wavelength tunability in 1.5–1.6 μm is necessary for meeting the application requirements in broadband tunable laser and optical amplifier as well as femtosecond ultrashort pulse laser. End-pumped by a continuous-wave 976.5 nm laser diode, the wavelength tunability of an Er:Yb:Ca3 NbGa3 Si2 O14 crystal with a broad and flat gain band in 1.5–1.6 μm was investigated. At an absorbed pump power of 7.4 W and a pump beam waist diameter of 200 μm, a continuously tunable 1.5–1.6 μm laser with a range of 83 nm was realized in the crystal. When the pump beam waist diameter was decreased to 100 μm, the wavelength tuning range of the laser increased to 102 nm. The obtained maximum continuous-wave output power was higher than 100 mW.